Assessment of the confiability and factorial structure of three scales measuring chronic procrastination - Argumedo Bustinza, Doris (2005)
This study explores the confiability and factorial structure of three scales measuring chronic procrastination: Scale of General Procrastination (EPG. Lay. 1986). Adult Procrastinatio Inventory (lPA. McCown & Johnson as cited in Ferrari. Johnson & McCown. 1995) and the Scale of Procrastination in Decision-Making (PTF. Mann. 1982). The sample included 514 adults between 20 and 65 years of age from Lima. The three scales showed high levels of intemal consistency and factorial analysis showed three factors for EPG and IPA and one factor for PTD A second degree factorial analysis suggested the presence of only one factor based on the grouping of items of the EPG and IPA scales The study did not find theoretically relevant dlfferences in chronic procrastination according to gender, age or education level. However,with respect to socioeconomic status. there were higher levels of chronic procrastmation in the poorest sector